Measurement of Well-Being in The Workplace: The Adaptation of The Workplace Well-Being Questionnaire Into Indonesian - Zamralita Zamralita; Anastasia Putri Leleng Wilis (Journal of Educational, Health and Community Psychology, 2026)
This study reports the adaptation and psychometric validation of an Indonesian-language version of the Workplace Well-Being Scale for use among active employees in Indonesia. The adaptation procedure adhered to the International Test Commission guidelines, incorporating forward–backward translation, expert panel review, and cognitive interviewing. Data were collected from 1,342 participants representing diverse occupational sectors, educational backgrounds, and organizational tenures. The four theorized dimensions—Work Satisfaction, Organizational Respect for the Employee, Employer Care, and Intrusion of Work into Private Life—were tested through confirmatory factor analysis. Internal consistency was strong across all subscales, with Cronbach's alpha coefficients ranging from .851 to .901. A second-order confirmatory factor analysis yielded an acceptable to good fit (incremental fit indices > .95; RMSEA = .089; GFI = .81; AGFI = .78), generally supporting the proposed hierarchical factor structure. Composite reliability (CR = .887–.919) and convergent validity (AVE = .531–.606) were satisfactory, although HTMT values among the three positive dimensions were borderline (.893–.898), indicating substantial conceptual overlap. These findings provide preliminary support for the Indonesian Workplace Well-Being Scale as a generally adequate instrument for assessing workplace well-being in Indonesian organizational contexts, though further refinement of model fit and examination of measurement invariance are needed.